Answer:
3.124 kilometers
Step-by-step explanation:
Answer:
see explanation
Step-by-step explanation:
Given
(x - 3) × (x + 4) = 0, that is
(x - 3)(x + 4) = 0
The zero product indicates that (x - 3) = 0 or (x + 4) = 0
x - 3 = 0 ⇒ x = 3
x + 4 = 0 ⇒ x = - 4
Thus if x = 3, then
(3 - 3)(x + 4) = 0 × (x + 4) = 0
Similarly if x = - 4 the output is zero
4x37
Step-by-step explanation:
only a few ways to get to 148
Answer:
x = 16
Step-by-step explanation:
5 = 1/2(x) - 3
Add 3 to both sides.
8 = 1/2(x)
Rewrite for clarity.
1/2(x) = 8
x/2 = 8
Multiply both sides by 2.
x = 16.
Proof:
5 = 1/2(x) - 3
Substitute variable.
5 = 1/2(16) - 3
Multiply 1/2 and 16.
5 = 8 - 3
Subtract 3 from 8.
5 = 5
Answer:
Option 4 is the image of the given figure.
Step-by-step explanation:
We are given that,
The shape EFGHCD is transformed to form another shape.
From the options, we see that,
Figure 2 and 3 does not have the same vertices as that of the figure.
So, they are discarded.
Since, after transforming a figure, we get a new figure.
So, the vertices cannot have same name as that of the original figure.
So, option 1 is discarded.
Thus, we get,
Option 4 is the image of the given figure after transformation as shown below.